Is Quantification of Measurable Clonal Plasma Cells in Stem Cell Grafts (gMRD) Clinically Meaningful? - Cengiz Seval, Guldane; Beksac, Meral (Frontiers in Oncology, 2022)
With the introduction of more effective novel therapies, the prognosis of multiple myeloma (MM) has improved significantly over the past decade, resulting with a significant proportion of patients achieving durable remissions that may reach even more than 10 years. Several studies demonstrated that the real prognostic value of complete remission (CR) relies on sustained undetectable minimal residual disease (MRD). Additionally, advance in MRD detection methods used for the detection of clonal plasma cells inside or outside the bone marrow have also improved the value of MRD. The use of peripheral blood for MRD detection could be an effective method that overcomes the spatial heterogeneity and invasive intervention with recurrent bone marrow aspirations. During the last two decades, many groups have investigated the role of circulating plasma cells (CPC) at diagnosis. As also presented by multiple groups during the recent ASH 2021 annual meeting, CPCs are becoming to be recognized as an independent prognostic factor. In addition, measurement of post-induction residual plasma cells in the stem cell graft is identified as another option for MRD assessment. Earlier studies in the era of less intensive induction regimens attempts to analyze the level of CPC contamination in the graft was shown to contribute to myeloma relapse and progression. According to these recent results, higher graft purity has been found to be in concordance with deeper responses. As expected, graft MRD (gMRD) may reflect the efficacy of induction as an additional response assessment tool. Although gMRD is a non-invasive approach it has not gained sufficient support for routine use. In view of the hurdles related to monoclonal protein assessments, high sensitivity cellular component measurement continues to possess its value as an end point for therapeutic efficacy. In this review, we will present a structural framework for MRD testing in peripheral blood stem cell autografts in MM and review the clinical integration into MM management.